Gambaran Pengetahuan dan Paparan Penyuluhan Terhadap Kepatuhan Protokol Covid-19 Pada Remaja Bandar Lampung - Yunus Elon; Fanny Dwi Rama Yani (CHMK NURSING SCIENTIFIC JOURNAL, 2021)
Corona Virus Disease (Covid-19) is a disease caused by the SARS-Cov2 virus and attacks the human respiratory system. Covid-19 is transmitted via respiratory droplets and contact with an incubation period of 1-14 days. Limited access to vaccines requires people to adhere to health protocols such as wearing masks, washing hands, maintaining distance, and getting enough rest and not panicking, and eating nutritious food. This study used a descriptive-analytic method with the aim of the study was to determine the description of knowledge and exposure to counseling on compliance with the Covid-19 protocol. The respondents of this study were 120 students of class X-XII SMA Immanuel Bandarlampung with a total sampling technique. The results showed that the level of knowledge, exposure to counseling, and compliance of respondents was high. The relationship test showed that there was no significant relationship between knowledge and exposure to counseling on compliance with the Covid-19 protocol in adolescents, especially adolescents in class X-XII SMA Immanuel Bandar Lampung.